# Step-by-step Solution

## Solve the equation $\frac{3x+1}{5x+7}=\frac{6x+11}{10x-3}$

Go!
Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

### Videos

$x=-\frac{5}{6}$

## Step-by-step Solution

Problem to solve:

$\frac{3x+1}{5x+7}=\frac{6x+11}{10x-3}$

Choose the solving method

1

Apply fraction cross-multiplication

$\left(3x+1\right)\left(10x-3\right)=\left(5x+7\right)\left(6x+11\right)$

Learn how to solve rational equations problems step by step online.

$\left(3x+1\right)\left(10x-3\right)=\left(5x+7\right)\left(6x+11\right)$

Learn how to solve rational equations problems step by step online. Solve the equation (3x+1)/(5x+7)=(6x+11)/(10x-3). Apply fraction cross-multiplication. Multiplying polynomials 3x+1 and 10x-3. Multiply the single term 10x by each term of the polynomial \left(3x+1\right). Multiply the single term -3 by each term of the polynomial \left(3x+1\right).

$x=-\frac{5}{6}$
SnapXam A2

### beta Got another answer? Verify it!

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

$\frac{3x+1}{5x+7}=\frac{6x+11}{10x-3}$